Semen quality and production potential of Indian buffalo breeds - BHAVE, K G; K, THILAK PON JAWAHAR; P, KUMARASAMY; P, KUMARASAMY; T, SIVAKUMAR; C, JOSEPH; SHENDE, V; KUNDALKAR, A; R, VENKATARAMANAN (The Indian Journal of Animal Sciences, 2021)
The objective of the study was to evaluate non-genetic factors on semen traits. The overall means for the semen quality traits: ejaculate volume, sperm concentration, total sperm, mass activity, initial and post thaw motility, hypoosmotic swelling test, acrosome integrity of fresh and frozen test were 4.39±0.01 ml, 1.29±0.001 billion, 5.48±0.01 billion, 2.55±0.003, 73.41±0.0004%, 55.9±0.0002%, 59.01±0.001%, 84.98±0.002% and 71.13±0.002%, respectively. Breeds were found to differ in all the semen production and quality traits studied except acrosome integrity of fresh semen. Summer for semen production, and winter and monsoon for semen quality traits were comparatively better season. The quality traits improved with age and declined slightly in the later life.